Diseño del sistema de iluminación LED en cancha de microfútbol de la Universidad Antonio Nariño sede sur, Bogotá (2020)
This project arises in response to the identification of certain technical parameters that did not comply with regulations, during the installation of the current lighting system in the recreational-sports space (micro-soccer field, UAN sede sur). For this reason, and through the use of specialized software (DIALux evo® and AutoCAD), a new artificial lighting system was designed using LED technology, which aims to improve current illuminance levels according to the volumetric conditions of the scenery and the luminous flux that it demands.